Development of A Build Up Training Model in Futsal Games - Oktarina; Fikri, Aprizal; Martinus; Hardiyono, Bayu; Hidayat, Arif; Riyoko, Endie; Harto, Agus Sugih (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Build up is an effort and process of attacking strategy by building an offensive strategy from various situations and conditions starting from the defensive line itself which aims to create goal opportunities and get victory. The purpose of this study is to produce a build-up training model in futsal games. The methods used in this study are the ADDIE analysis, design, developmet, implementation, and evaluation methods. The results of this study were obtained from the expert validation that had been carried out involving 3 experts including 1 futsal coach, 1 futsal academic, and 1 futsal practitioner. This research instrument uses a questionnaire. Based on the results of the CVI and CVR analysis, a value of 0.5 or valid. It can be interpreted that this build up session 1 training model is feasible to use and applied to the build up training of futsal club athletes in the city of Palembang